American Buffalo - Mamet, David; Kite, Brian; DuBrow, Donny; Stamberg, Josh; Williams, Maurice; L.A. Theatre Works ([Venice, California] : L.A. Theatre Works, 2016)
A classic tragedy, American Buffalo is the story of three men struggling in the pursuit of their distorted vision of the American Dream. By turns touching and cynical, poignant and violent, American Buffalo is a piercing story of how people can be corrupted into betraying their ideals and those they love.
"Directed by Brian Kite and recorded before an audience by L.A. Theatre Works."--Container.
Director, Brian Kite ; producing director, Susan Albert Loewenberg ; recording and mixing engineer, Mark Holden.
Narrated by Anne Archer, Kurt Ehrmann, Jennifer Friedmann, Lily Shaw and David Tierney.
Keywords: American Dream -- Drama; Thieves -- Drama; Loyalty -- Drama; Idealism, American -- Drama; American Dream; Idealism, American; Loyalty; Thieves; Audiobooks; Live sound recordings; Audiobooks; Drama; Live sound recordings